2009
DOI: 10.1007/s00542-009-0785-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of a normally closed glucose sensitive hydrogel based microvalve

Abstract: In drug delivery systems microvalves are the key components that have been developed for active control of drugs. In this research a normally closed microvalve with a glucose sensitive hydrogel actuating system is designed and simulated. Swelling of the hydrogel forces a silicone rubber membrane to deflect and causes the valve to be opened. The component of the valve that can be opened because of the hydrogel pressure is a silicon nitride cantilever beam which is sealed with a parylene layer. Simulations have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…While the porous nature of hydrogel polymers has been utilized in other applications that include dialysis, gel electrophoresis, sample separation, and tissue engineering, it is their mechanical response to external stimuli that makes them attractive for microvalves actuation schemes. The expansion and contraction of hydrogels under external stimuli has been used to regulate the flow liquids in variety of microfluidic systems 12,13 . While other hydrogel based microvalves have been presented that employ thermally responsive diaphragm actuators very similar to the device presented here 14 , these devices have employed traditional MEMS resistance microheaters on non-flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…While the porous nature of hydrogel polymers has been utilized in other applications that include dialysis, gel electrophoresis, sample separation, and tissue engineering, it is their mechanical response to external stimuli that makes them attractive for microvalves actuation schemes. The expansion and contraction of hydrogels under external stimuli has been used to regulate the flow liquids in variety of microfluidic systems 12,13 . While other hydrogel based microvalves have been presented that employ thermally responsive diaphragm actuators very similar to the device presented here 14 , these devices have employed traditional MEMS resistance microheaters on non-flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their potential for active flow control, numerous experimental designs and studies of hydrogels as flow controller in microfluidic systems have been conducted [ 15 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In contrast, few studies concerning mathematical modeling and simulation have been reported [ 28 , 29 , 30 ]; hence, it is of interest to develop mathematical models which can aid in the synthesis and design of hydrogels as microfluidic flow controllers.…”
Section: Introductionmentioning
confidence: 99%